Critical view of safety in laparoscopic cholecystectomy: A prospective investigation from both cognitive and executive aspects - Jin, Yi; Liu, Runwen; Chen, Yonghua; Liu, Jie; Zhao, Ying; Wei, Ailin; Li, Yichuan; Li, Hai; Xu, Jun; Wang, Xin; Li, Ang (Frontiers in Surgery, 2022)
Background The achievement rate of the critical view of safety during laparoscopic cholecystectomy is much lower than expected. This original study aims to investigate and analyze factors associated with a low critical view of safety achievement. Materials and Methods We prospectively collected laparoscopic cholecystectomy videos performed from September 2, 2021, to September 19, 2021, in Sichuan Province, China. The artificial intelligence system, SurgSmart, analyzed videos under the necessary corrections undergone by expert surgeons. Also, we distributed questionnaires to surgeons and analyzed them along with surgical videos simultaneously. Results We collected 169 laparoscopic cholecystectomy surgical videos undergone by 124 surgeons, among which 105 participants gave valid answers to the questionnaire. Excluding those who conducted the bail-out process directly, the overall critical view of safety achievement rates for non-inflammatory and inflammatory groups were 18.18% (18/99) and 9.84% (6/61), respectively. Although 80.95% (85/105) of the surgeons understood the basic concept of the critical view of safety, only 4.76% (5/105) of the respondents commanded all three criteria in an error-free way. Multivariate logistic regression results showed that an unconventional surgical workflow (OR:12.372, P < 0.001), a misunderstanding of the 2nd (OR: 8.917, P < 0.05) and 3rd (OR:8.206, P < 0.05) criterion of the critical view of safety, and the don't mistake “fundus-first technique” as one criterion of the critical view of safety (OR:0.123, P < 0.01) were associated with lower and higher achievements of the critical view of safety, respectively. Conclusions The execution and cognition of the critical view of safety are deficient, especially the latter one. Thus, increasing the critical view of safety surgical awareness may effectively improve its achievement rate.